Giving what they want: How congruence between expected feedback quality and delivered feedback quality influences leader-member exchange and job performance - Qi, Qi; Liu, Yanyan; Liu, Zhaoyan (Frontiers in Psychology, 2023)
As an attempt to solve the mixed results between leader feedback quality and employee job performance, this study proposes that employees’ expected feedback quality plays a key role in how employees react to leader feedback. Specifically, drawing on needs-supplies fit and social exchange theory, we posit that congruence between expected feedback quality and delivered feedback quality positively relates to employee task performance and organizational citizenship behaviour (OCB) through leader-member exchange (LMX). Further, we posit that learning goal orientation may strengthen the positive effect of congruence between expected feedback quality and delivered feedback quality on LMX. Multi-wave data collected from 226 employees from China showed that congruence between expected feedback quality and delivered feedback quality improves LMX and in turn benefits task performance and OCB. Moreover, learning goal orientation intensifies the indirect effect of congruence between expected feedback quality and delivered feedback quality on task performance and OCB through LMX. The theoretical and practical implications of these findings are discussed.